Improvement in gait asymmetry during Nordic walking in patients with lower extremity osteoarthritis - Noriaki Kato; Chiho Fukusaki; Kannika Leetawesup; Yuma Kadokura; Naokata Ishii (Japanese Society of Physical Fitness and Sports Medicine, 2020)
Gait asymmetry is a problem in patients with lower extremity osteoarthritis because a larger load on one leg is associated with the risk of future arthritic deterioration in that leg. Therefore, amelioration of gait asymmetry is desirable for such patients. The present study aimed to investigate whether gait asymmetry is reduced during Nordic walking (NW) in patients with lower extremity osteoarthritis. Sixteen patients wore inertial sensors and performed a 15-m walk test with and without poles. Step symmetry and stride regularity were calculated using an autocorrelation sequence of trunk acceleration to evaluate gait symmetry and regularity, respectively. Maximal isometric knee extension strength was measured in both legs, and leg strength asymmetry was determined. NW improved step symmetry in the anterior-posterior (P = 0.005) and vertical (P = 0.015) directions. Patients were divided into two groups based on leg strength asymmetry. In patients with larger leg strength asymmetry, step symmetry was lower in the anterior-posterior and vertical directions during walking without poles (P = 0.005, P = 0.002, respectively). This was improved during NW (P = 0.005, P = 0.015, respectively). In patients with smaller leg strength asymmetry, there were no significant improvements in step symmetry or stride regularity during NW. These results suggest that NW improves gait asymmetry and can be an effective approach to prevent arthritic deterioration, especially in patients with large leg strength asymmetry.